Simbolisasi Pakaian Adat dalam Kirab Sedekah Laut Cilacap: Analisis Semiotika Roland Barthes - Maulana, Taofik; Afandi, Titah; Nur Afifah Hamzah (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2025)
This study aims to examine the symbolic meaning represented in traditional clothing used during the sedekah laut procession in Cilacap. The method used in this study is a qualitative descriptive method. The research data is in the form of documentation and information from resource persons. The data analysis technique uses Roland Barthes’ semiotics approach. The results of the study show that the traditional clothes used during the sedekah laut procession can be grouped into four, namely maggalayudha clothes, putri domas clothes, traditional fisherman clothes, and woman clothes that are prepared to be used as offerings. All of these traditional clothes have denotative meanings and also connotative meanings which leads to the conclusion that the traditional clothes worn by the participants of the sedekah laut carnival are not just traditional clothes, but also a complex system of signs that contain various cultural, spiritual, and ideological meanings.